Impact of Source Variability and Hydrodynamic Forces on the Distribution, Transport, and Burial of Sedimentary Organic Matter in a Tropical Coastal Margin: The Gulf of Thailand. Issue 9 (18th September 2021) - Bai, Yazhi; Hu, Limin; Wu, Bin; Qiao, Shuqing; Fan, Dejiang; Liu, Shengfa; Yang, Gang; Liu, Jihua; Kornkanitnan, Narumol; Khokiattiwong, Somkiat; Shi, Xuefa
Abstract: Carbon cycling in the tropical margin is more extensive compared with other regions of the world. The goal of this study was to better understand the origins, transport, and burial of sedimentary organic matter (SOM) in the Gulf of Thailand (GOT) from the coastal margin of Southeast (SE) Asia, which serve as a major depository of ﬁne‐grained sediments and the associated organic carbon (OC). The results revealed a variety of organic matter (OM) inputs and the selective transport of fine sediment, resulting in preferential dispersal of terrigenous SOM in the GOT. Bulk OC indices with low carbon/nitrogen ratios and enriched stable carbon isotope ratios (−24.2‰ to −20.4‰, and mean −21.4 ± 0.56‰) are likely related to the presence of marine‐derived OM and anthropogenic interference. A binary mixing model further clarified the significant contributions of terrestrial derived‐OM within the upper and central GOT. The n ‐alkane compositions and principal component analysis indicated that a majority of the terrigenous SOM settles within the estuary in the upper GOT, while a selective dispersal of land‐based SOM through long‐distance transport toward the modern depocenter in the lower GOT. The characteristics of lower molecular weight n ‐alkanes also suggest anthropogenic OM input from petroleum‐related contributions. Altogether, the depositional patterns and spatial heterogeneity of the SOM indicated by both the bulk and molecular signatures reveal the important roles of source variability and the selective dispersal of land‐based OM on the supply and accumulation of OC in the tropical coastal margin. Plain Language Summary: The accumulation and fate of sedimentary organic carbon (OC) in the tropical coastal system are significant components of the global carbon cycling. In order to elucidate the distribution and accumulation of organic matter (OM) in tropical regimes, this study first explored the concentration and composition of sedimentary OC based on the bulk and molecular‐level data, and then depicted the modern transport pattern of OM in the Gulf of Thailand (GOT). This study showed terrestrial input accounted for 5%–64% (20% ± 8% on average) of the OM and dominated in the upper GOT, the offshore depocenter in the northeastern GOT and north of Samui Island. Molecular composition of n‐alkanes and principal component analysis result showed that the hydrodynamic condition plays a significant role on the selective dispersal of terrigenous OM from the coastal region to the offshore depocenter. In addition, the contribution from petroleum‐derived OM is also revealed based on the molecular‐level evidences. The spatial heterogeneity of OM revealed the variability of the sources and hydrodynamic forces on accumulation and fate of OM in the tropical coastal margins Key Points: The bulk organic matter (OM) signals indicate spatial heterogeneity of various OM contributions to the Gulf of Thailand (GOT) The molecular‐level OM compositions suggest a selective dispersal of terrigenous sedimentary organic matter (SOM) toward fine sediment depocenter in the central GOT Source variability and hydrodynamic forces regulate the accumulation and fate of SOM in the tropical coastal margin